(untitled) (Research, Society and Development, 2024)
Alloimmunization is the production of antibodies against antigens considered non-self, a reaction observed mainly in patients who have received multiple transfusions and in pregnant women. When related to pregnancy, the consequences of isoimmunization depend on several factors, the main one being antigenic incompatibility, due to the presence of different substances on the surfaces of the red blood cells of the fetus and the mother. This was an narrative literature review, carried out through: Scientific articles, virtual journals, bibliographic research and databases, such as Scielo and Google Scholar, collected between 2015 and 2024, in Portuguese and English. Based on the analysis of the information obtained through the selected studies, the following themes were categorized: Phenotypic frequency according to the Rh system; Incidence of Alloimmunization; Prevalence of cases of Hemolytic Disease of the Fetus and Newborn; Use of anti-D Immunoglobulin in Rh-negative pregnant women; Effectiveness of treatment measures; And the importance of early diagnosis and adequate care. The preparation of this work showed that Hemolytic Disease of the Fetus and Newborn is a highly complex pathology and its characterization has significant relevance for the population, given its degree of severity if not diagnosed and treated early.